Pelvic congestion syndrome: increasing awareness is the key to facilitating proper diagnosis and appropriate treatment - Giulia Maria Piermarini; Ottavia Borghese; Yamume Tshomba (Veins and Lymphatics)
Pelvic Congestion Syndrome (PCS) represents a complex and frequently misdiagnosed disease that may greatly impact on quality of life of affected patients.